Description of Market Sanitation Conditions in Kupang City in 2021 - Lesiangi, Melliyanti Omi Ribka; Salmun, Johny A. R; Dodo, Dominirsep O (Lontar : Journal of Community Health, 2023)
Supervision and inspection of sanitation in public places help protect public health from the possibility of disease transmission and other health problems. Market sanitation is one part of the effort to monitor and inspect public areas' sanitation. The market is still the primary choice for some people to buy daily necessities because the goods sold, especially vegetables, fruits, and meat, tend to be fresher and cheaper. Market Sanitation aims to reduce the risk of health problems in the market environment. This study aims to determine the market sanitation conditions in Kupang City in 2021. The type of research used is descriptive research with a survey approach or method. The population is the entire market in Kupang City. The samples in this study were Kasih Market, Oeba Market, Oebobo Market, Oesapa Market, and Penfui Market. Sampling using a purposive sampling technique. The data obtained were analyzed using univariate analysis. The results showed that the sanitary conditions of the market do not meet the requirements. The sanitary conditions are buildings, stalls, waste disposal sites, drainage, toilets, clean water, places for selling foods and groceries, animal control of disease transmission, market safety, lighting, temperature and humidity, hand-washing places, parking lots, clean and healthy living behavior of traders and visitors at Kasih Market, Oeba Market, Oebobo Market, Oesapa Market, and Penfui Market. Therefore, market managers are expected to be able to improve market sanitation conditions under predetermined conditions.